Development and Evaluation of Performance Measures for Capacity Utilization of Traffic Signals. Issue 1 (January 2023) - Dobrota, Nemanja; Stevanovic, Aleksandar; Mitrovic, Nikola; Alshayeb, Suhaib; Zlatkovic, Milan
Emerging high-resolution datasets allow for developing traffic signal performance measures (TSPMs) which can provide a better understanding of traffic signal operations. One of the specific objectives of signal operations is related to the measurement of capacity utilization. A fundamental measure for capacity utilization is the "degree of saturation" ( DS ), and it has both volume-based and occupancy-based formulations. The former is known as "volume over capacity ratio" ( V/C ), whereas the latter is known as "green occupancy ratio" ( GOR ). When V/C is used to observe capacity utilization, it is not known whether the capacity is utilized from interrupted flow, free flow, or a combination of two. Similarly, the amount of time in the cycle utilized by volume (characterized with the first and last vehicle arrival time) is not revealed within V/C . On the other hand, GOR "overlooks" cases when a high number of vehicles travel without stopping or fewer vehicles depart the signal with significant startup delays and similar. In addition, because of a lack of scientific attention, GOR has often been misinterpreted as some similar, yet different TSPM. Therefore, if only V/C or GOR are used to monitor signal performance, the understanding of utilized capacity will be incomplete or misleading. This study proposes three TSPMs: "queued volume in volume to capacity ratio" ( QViV/C ), "cycle utilization" ( CLU ), and "volume-occupancy capacity utilization" ( VOCU ) to overcome the limitations of V/C and GOR . Also, by evaluating existing occupancy-based measures, it was found that they can be used to estimate capacity utilization, including oversaturated conditions.